2006
DOI: 10.1007/s11244-006-0124-4
|View full text |Cite
|
Sign up to set email alerts
|

Titanium-monosubstituted polyoxometalates: relation between homogeneous and heterogeneous Ti-single-site-based catalysis

Abstract: The similarity in the catalytic behaviour of titanium-monosubstituted Keggin type polyoxometalates [PTi(L)W 11 O 39 ] n-(TiPOMs) and heterogeneous titanium single-site catalysts in selective oxidations with H 2 O 2 is demonstrated. Recent achievements in the application of Ti-POMs as soluble molecular models for studying mechanisms of oxidation catalysis are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 182 publications
(299 reference statements)
1
29
0
Order By: Relevance
“…For the sake of completeness, we should also mention other types of SSHCs that fall into the first category, namely certain polyoxometalates (Kholdeeva 2006), pillared clays (Jones 1985) and also the fascinating extra-framework cations in zeolites, which is the subject of the article in this issue by Pidko et al (2012). While it has long been known that La 3+ ions located as extra-framework entities in zeolite-Y constitutes one of the most powerful catalytic cracking (in hydrocarbons) catalyst-see Thomas (2011) and Schüssler et al (2011) Figure 2.…”
Section: Definition Of a Single-site Heterogeneous Catalystmentioning
confidence: 99%
“…For the sake of completeness, we should also mention other types of SSHCs that fall into the first category, namely certain polyoxometalates (Kholdeeva 2006), pillared clays (Jones 1985) and also the fascinating extra-framework cations in zeolites, which is the subject of the article in this issue by Pidko et al (2012). While it has long been known that La 3+ ions located as extra-framework entities in zeolite-Y constitutes one of the most powerful catalytic cracking (in hydrocarbons) catalyst-see Thomas (2011) and Schüssler et al (2011) Figure 2.…”
Section: Definition Of a Single-site Heterogeneous Catalystmentioning
confidence: 99%
“…In contrast, titanium-substituted polyoxometalates (POMs) have inorganic nature, are thermodynamically stable to oxidation, and possess hydrolytic stability under appropriate pH conditions, which makes them suitable molecular models for Ti centers in aqueous-organic media. [5] The apparent structural analogy of POMs and metal oxide surfaces allows one to view POMs as discrete, soluble fragments of extended metal oxide lattices. [6] Recently, Kholdeeva et al demonstrated that the catalytic performance of tetra-n-butyl ammonium (TBA) salts of titaniummonosubstitutedKeggin-typeheteropolytungstates,(Bu 4 N) 4 -[PTi(L)W 11 O 39 ] (Ti-POM), in the oxidation of alkenes, thioethers, and alkylphenols with H 2 O 2 is very similar to that of hydrophilic mesoporous titanium silicate catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of water, coordination of H2O molecules to the Ti _ OOH active species forms cyclic structures. Previous reports 20) and Hammett plots indicate the reaction mechanism occurs as follows (Fig. 4).…”
Section: Recyclable Titanosilicate Zeolite Catalyst Formentioning
confidence: 67%
“…The use of solid titanosilicate zeolite catalysts, such as TS-1 and Ti-MWW, is very effective for achieving high-yield syntheses of various sulfoxides and sulfones for industrial processes, due to easy separation and reusability. Titanosilicate zeolite catalysts in the presence of H2O2 can oxidize sulfides to give sulfoxides and sulfones 20) . However, the relationship between zeolite structure and reactivity has not been investigated.…”
Section: Recyclable Titanosilicate Zeolite Catalyst Formentioning
confidence: 99%
See 1 more Smart Citation